2011
DOI: 10.1186/1471-2458-11-514
|View full text |Cite
|
Sign up to set email alerts
|

Contributions and challenges of cross-national comparative research in migration, ethnicity and health: insights from a preliminary study of maternal health in Germany, Canada and the UK

Abstract: BackgroundPublic health researchers are increasingly encouraged to establish international collaborations and to undertake cross-national comparative studies. To-date relatively few such studies have addressed migration, ethnicity and health, but their number is growing. While it is clear that divergent approaches to such comparative research are emerging, public health researchers have not so far given considered attention to the opportunities and challenges presented by such work. This paper contributes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…180 It is not, therefore, surprising to find that our review yielded rather inconsistent evidence on the association between (minority) ethnicity and attendance behaviour. Furthermore, compared with measures of deprivation, race/ethnicity appears to have been less often considered in attendance research, particularly outside the USA.…”
Section: Ethnicitymentioning
confidence: 82%
“…180 It is not, therefore, surprising to find that our review yielded rather inconsistent evidence on the association between (minority) ethnicity and attendance behaviour. Furthermore, compared with measures of deprivation, race/ethnicity appears to have been less often considered in attendance research, particularly outside the USA.…”
Section: Ethnicitymentioning
confidence: 82%
“…Immigrant women having recently arrived in their host country and with poor social networks, limited language proficiency and lack of knowledge about accessing or inability to legitimately access medical or obstetric care are at the greatest risk for receiving poor maternity care (Sanmartin and Ross, 2006;Sword et al, 2006a;Hayes et al, 2011). A previous report has indicated that potential barriers for receiving effective Contents lists available at ScienceDirect journal homepage: www.elsevier.com/midw Midwifery health care in the United Kingdom (UK), Canada and Germany may include cultural misunderstandings, communication problems and racism (Salway et al, 2011). Other international studies include those in the United Kingdom (UK) looking at variables related to maternal morbidity and mortality (Ameh and Van den Broek, 2008;Knight et al, 2009) which found that black and ethnic minority women who do not access or receive optimal care can have higher risk of morbidity and death, partly due to factors related to care during pregnancy, labour, and birth.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in continental Europe are more wary of collecting data on participants' ethnicity and tend to categorize ethnicity by the country of origin of, and/or the language spoken by, participants and/ or their parents (Verkuyten, 2009). Ethnicity can be an important variable in terms of vulnerability, but these definitional inconsistencies raise issues over the validity of given categorizations and intercountry comparisons (Salway et al, 2011).…”
Section: Tertiary Ethical Proceduresmentioning
confidence: 99%